Development of GMP and HACCP protocol for pepper industry - PRITTY S. BABU SARATHJITH M.C TINA ANN ABRAHAM; Dr. Sudheer K.P (Guide) (Tavanur 2009 Kelappaji College of Agricultural Engineering and Technology)
Development of GMP and HACCP protocol for pepper industry
Development of GMP and HACCP protocol for pepper industry